Instalación de una turbina tipo turgo para el Centro de Investigaciones de Energías Renovables y Eficiencia Energética CIEREE, de la Universidad Nacional de Loja. - Merizalde Merchán, José Henry. (2013)
This paper aims to present a selection methodology and calculation for hydraulic and mechanical design of the main parts of a turbine Turgo as well as the various elements of this machine. This is part of the fundamental principles of hydraulic turbines, previous studies Turgo turbines specifically, information provided by manufacturers of these machines, as well as knowledge of mechanical strength, design of machine elements, building materials for these turbines inter alia. The turbine installation for Turgo type (CIEREE) it is performed with the goal of having students take tests on micro-hydro and catch up on the best and most economical way to generate their own energy through the fall of water. This turbine has many advantages since it could be used in deserted places where lack of electric power, which is important to the low cost and ease of installation. In conclusion we can say that the installation of this turbine would be of great help to the students of this University for conducting such tests disseminate implement them throughout society and give the deputy minister to all fa need.